The Art of Paradox in Wafai’s Poems (Raparin Journal of Humanities (RJH), 2021)
The paradox is an artistic expression used for beautifying the poetic language, the poems of Kurdish poets like Arabic, Persian, and Western nations include these arts and the plays of the poetic language. This type of poetic art can be seen noticeably in every era of the Kurdish classic poems which is a reason for enriching and empowering the poetic language. It will also, produce modern imagination and expressions which will be thoughtful and speculative and it will attract readers’ attention due to its’ closeness to the contradictory art which is again a type of beautifying the semantic art. According to the earlier researches in this field, paradoxical art is a type of contradictory art but it has specific liberty by itself. The appearance of paradoxical expressions will be in the shape of semantical, lexical, and in one or two sentences. The Diwan of Wafay was focused on for this research amongst the diwans of classical Kurdish poets. Wafay (1844-1904) was a poet in the second half of the nineteenth century and the beginning of the twentieth. He had a warm poetic language and meaningful and vivid sentences. His poems are full of semantics and lexical artistic beautifications. For this purpose, the researcher will investigate the placement shapes of the generic paradoxical composition and analyzing them according to grammar and rhetorical in Wafay’s poems.